Acoustic pulse propagation in an urban environment using a three-dimensional numerical simulation - Mehra, Ravish; Raghuvanshi, Nikunj; Chandak, Anish; Albert, Donald G.; Wilson, D. Keith; Manocha, Dinesh (Journal of the Acoustical Society of America, 2014)
Acoustic pulse propagation in outdoor urban environments is a physically complex phenomenon due to the predominance of reflection, diffraction, and scattering. This is especially true in non-line-of-sight cases, where edge diffraction and high-order scattering are major components of acoustic energy transport. Past work by Albert and Liu [J. Acoust. Soc. Am. 127, 1335–1346 (2010)] has shown that many of these effects can be captured using a two-dimensional finite-difference time-domain method, which was compared to the measured data recorded in an army training village. In this paper, a full three-dimensional analysis of acoustic pulse propagation is presented. This analysis is enabled by the adaptive rectangular decomposition method by Raghuvanshi, Narain and Lin [IEEE Trans. Visual. Comput. Graphics 15, 789–801 (2009)], which models sound propagation in the same scene in three dimensions. The simulation is run at a much higher usable bandwidth (nearly 450 Hz) and took only a few minutes on a desktop computer. It is shown that a three-dimensional solution provides better agreement with measured data than two-dimensional modeling, especially in cases where propagation over rooftops is important. In general, the predicted acoustic responses match well with measured results for the source/sensor locations.